PERSEPSI DAN PARTISIPASI MASYARAKAT TERHADAP LOCAL GUIDE DI DESA OHOIDERTAWUN DAN DESA OHOILILIR - Maria Magdalena Ngamelubun; Wiwien Gaby Hukubun (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2017)
Local luide has an important role in the development of tourism in the region. This is shows by the number of tourists visiting. Therefore, local guides available in tourism ohoi (village) located in Kei island must have a good English skill in order to explain or provide information about their area. Beside that, a local guide should also have insight or skill in tour guiding so that they can be able to guide tourists who visit the area. This research aims to obtain the data about the perception of the people about local guide, and their participation to be a local guide. This research uses descriptive qualitative method. The location of this research is in Ohoidertawun and Ohoililir. Data collection technique is conducted by using questioner, interview and documentation. The results of this study shows that local guide owned by local tourism Ohoi is still 'less' in terms of communicating using English to communicate with foreign tourists. Thus, the local guide is still required to obtain English tourism training and guiding tour techniques.